Classifying young soccer players by training performances - Abade, E. A.; Goncalves, B. V.; Silva, A. M.; Leite, N. M.; Castagna, C.; Sampaio, J. E. (Perceptual and Motor Skills, 2014)
Players within the same age group may present different physical and physiological profiles. This study classified young soccer players according to their physical and physiological profiles obtained during the training sessions and compared classification by age and playing position criteria. 151 male elite Portuguese soccer players (under 15, under 17, and under 19 years old) participated. Time-motion and body acceleration and deceleration data were collected using GPS technology with heart rate monitored continuously across the selected training sessions. The data were grouped using two-step cluster analysis to classify athletes. A repeated-measures factorial ANOVA was performed to identify differences in the variables. Three clusters comprised 15.2%, 37.1%, and 47.7% of the total sample, respectively. Players of the same ages and playing experience had different performance profiles. Grouping players with similar physiological profiles during training sessions may allow coaches to balance oppositions and reduce the variability of the physiological outcomes.